Analysis of Zakat, Infaq, and Alms Fundraising Policy Through IRAC Method - Wahyuni, Sri; Mahardika, Swadia Gandhi; Pramono, Adi Tri (Jurnal Ilmiah Akuntansi Kesatuan, 2025)
This study analyzes the Zakat, Infaq, and Sedekah (ZIS) fundraising model in Bontang City with a focus on the policy of zakat deductions from the salaries of State Civil Apparatus (ASN) based on the Mayor's Regulation in 2013. The approach used is a juridical-normative approach with the IRAC (Issue, Rule, Analysis, and Conclusion) method to influence treatment and identify the optimal potential of ZIS. The results of the study indicate that although the mandatory zakat policy for ASN has been implemented, its contribution to increasing ZIS funds is still limited. This is because the regulation does not yet cover employees of State-Owned Enterprises (SOEs) and the private sector which have great potential in increasing zakat collection. This study also compares previous findings which show that countries with zakat regulations that are inclusive of the private sector have higher levels of compliance and fund acquisition. Therefore, regulations that cover SOEs employees and large companies in Bontang City are considered important to optimize ZIS fund collection. A more inclusive policy will strengthen zakat distribution programs, support poverty alleviation, education, and community economic empowerment.